O propozicijskosti prislovov v slovenščini (z vidika slovanskega jezikoslovja) - Žele, Andreja (Slavia Centralis, 2020)
On Proposition in Adverbs in Slovene (from Aspect of Slavic Linguistics)Since we generally consider adverbs as organic components of clause's structural integrity their broad array of use or transition from proposition to non-proposition, and vice versa, is nothing special. Apart from real adverbs of time and place, definite adverbs also rank among independent components of the proposition. They fall under semantic necessity that is tied to valency, because only those participants who have a concrete (denotative and referential) are essential components of proposition and may serve to introduce valency.
Keywords: proposition; propositional components; adverbs; wording